PENGARUH KOMPENSASI DAN KOMPETENSI TERHADAP KOMITMEN ORGANISASI SERTA IMPLIKASINYA PADA KINERJA TENAGA AHLI PERUSAHAAN JASA KONSTRUKSI DI PROVINSI JAMBI - Fakhrul Rozi Yamali; Fakhrul Rozi Yamali (Ekonomis: Journal of Economics and Business, 2017)
The purpose of this research is to find out and analyze the effect of compensation and competency of either partially or jointly towards organizational commitment. Then the influence of the compensation, competence and commitment of the Organization partially or jointly on performance experts. The population in this study of 1,321 people construction services company experts in the province of Jambi. The methods used in this research is a descriptive survey method and sample survey of eksplanatori with the spread as much as 265 respondents. Based on the results of the hypothesis, compensation and competency as well as partially positive and significanteffect together toward organizational commitment (KO) and R2 = 0.53 or account for 53%, and partially compensation effect positive and insignificant against the performance experts (KA), competence and commitment of the Organization of the partially positive and significant effect on performance experts (KA) while the compensation, competence and commitment of the Organization in together the positive and significant effect on performance experts (KA) and R2 = 0.52 or account for 52%Keywords: Compensation, Organizational Commitment, Competence, Performance Experts